1979
DOI: 10.1093/infdis/139.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Non-B Hepatitis in Japanese Recipients of Blood Transfusions: Clinical and Serologic Studies after the Introduction of Laboratory Screening of Donor Blood for Hepatitis B Surface Antigen

Abstract: Cases of hepatitis virus infection in Japanese recipients of blood transfusions were serologically and clinically analyzed after the introduction of laboratory screening of donor blood for hepatitis B surface antigen by counter immunoelectrophoresis. Non-A, non-B hepatitis occurred in 116 (10.7%) and hepatitis type B in nine (0.9%) of the 1,082 recipients. The incubation period of the post-transfusion non-A, non-B hepatitis cases varied from two to 33 weeks, but most occurred within 15 weeks. In 97 (83.6%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
2

Year Published

1980
1980
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 22 publications
2
13
2
Order By: Relevance
“…In our center there has been no increase in the number of overt non-A, non-B cases during 1974-1978, which in part contrasts with reports from the USA [8], Germany [6] and Japan [9]. According to these reports, a considerable increase in the fre quency of non-A, non-B hepatitis cases fol lowing transfusions has been noted.…”
contrasting
confidence: 80%
“…In our center there has been no increase in the number of overt non-A, non-B cases during 1974-1978, which in part contrasts with reports from the USA [8], Germany [6] and Japan [9]. According to these reports, a considerable increase in the fre quency of non-A, non-B hepatitis cases fol lowing transfusions has been noted.…”
contrasting
confidence: 80%
“…Definite hepatitis was noted in 205 cases (10.3%) and probable hepatitis in 246 cases (12.4%). The incidence of posttransfusion hepatitis in the present study exceeded that reported in several previous studies [3,[12][13][14][20][21][22], as summarized in table 10. Abnormal ALT in 2 consecutive blood specimens was needed for the diagnosis of posttransfusion hepatitis in the studies of Al ter et al…”
Section: Risk Factors Of Donated Bloodcontrasting
confidence: 48%
“…Viral hepatitis commonly occurs in the absence of ser ologic markers for such known hepatotropic agents as hep atitis A virus (HAV), hepatitis B virus (HBV), cytomegalo virus (CMV) and Epstein-Barr virus (EBV) [1][2][3][4]. This entity termed non-A, non-B hepatitis (NANB) accounts for more than 90% of transfusion-associated hepatitis cases worldwide [5,6].…”
Section: Introductionmentioning
confidence: 99%